2012
DOI: 10.1007/s00158-012-0856-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical optimization of pacing strategy in cross-country skiing

Abstract: This is an accepted version of a paper published in Structural and multidisciplinary optimization (Print).Citation for the published paper: Sundström, D., Carlsson, P., Ståhl, F., Tinnsten, M. (2012) "Numerical optimization of pacing strategy in cross-country skiing" Structural and multidisciplinary optimization (Print) URL: http://dx.doi.org/10.1007/s00158-012-0856-7Access to the published version may require subscription. AbstractWhen studying events involving locomotive exercise, such as cross-country skii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…They found performance benefits from all ''all-out'' start and thereafter even pacing. Sundstrøm et al (2013) similarly found that ''an optimal pacing strategy is characterized by minor variations in speed'', determined numerically by a nonlinear optimization routine. Applied to this paper's model this suggests a constant or relatively constant intensity parameter e through varying terrain (except steep downhill where intensity inevitably decreases), and intensity inverse proportional to track length.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They found performance benefits from all ''all-out'' start and thereafter even pacing. Sundstrøm et al (2013) similarly found that ''an optimal pacing strategy is characterized by minor variations in speed'', determined numerically by a nonlinear optimization routine. Applied to this paper's model this suggests a constant or relatively constant intensity parameter e through varying terrain (except steep downhill where intensity inevitably decreases), and intensity inverse proportional to track length.…”
Section: Discussionmentioning
confidence: 96%
“…For speeds above 10 m/s skiers usually use techniques such as the tuck position to save energy (Andersson et al, 2010). Using these insights locomotive power has recently been analyzed as a function of speed only (Moxnes et al, 2014;Sundstrøm et al, 2013). This paper's contribution is to endogenize locomotive power more thoroughly into power production, in the sense of making locomotive power a variable in the model instead of an exogenously given parameter.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This acceleration was estimated from the measured speed as an average between the measured values. The OP estimate is based on the numerical optimization model of Sundström et al [11] which is based on the same mechanical model as Carlsson et al [12]. The OP estimate uses the method of moving asymptotes [13] and varies the power output to minimize the square of speed difference between the mechanical model and the actual performance of a cross-country skier on a treadmill.…”
Section: Power Output Estimatesmentioning
confidence: 99%
“…(1)- (5)] projected onto these directions. Subsequently, the equations of motion were transformed according to Sundström et al [21] to make distance ( ) the dependant variable and time the independent variable. Consequently, the equation of motion was expressed as: +tan cos +( )2 1 cos + 2 (6) where is time and prime denotes differentiation by .…”
Section: Equations Of Motionmentioning
confidence: 99%